Rapid CVD growth of millimetre-sized single crystal graphene using a cold-wall reactor. (20th January 2015) - Miseikis, V; Convertino, D; Mishra, N; Gemmi, M; Mashoff, T; Heun, S; Haghighian, N; Bisio, F; Canepa, M; Piazza, V; Coletti, C
Abstract: In this work we present a simple pathway to obtain large single-crystal graphene on copper (Cu) foils with high growth rates using a commercially available cold-wall chemical vapour deposition (CVD) reactor. We show that graphene nucleation density is drastically reduced and crystal growth is accelerated when: (i) using ex situ oxidized foils; (ii) performing annealing in an inert atmosphere prior to growth; (iii) enclosing the foils to lower the precursor impingement flux during growth. Growth rates as high as 14.7 and 17.5 μ m min −1 are obtained on flat and folded foils, respectively. Thus, single-crystal grains with lateral size of about 1 mm can be obtained in just 1 h. The samples are characterized by optical microscopy, scanning electron microscopy, x-ray photoelectron spectroscopy, Raman spectroscopy as well as selected area electron diffraction and low-energy electron diffraction, which confirm the high quality and homogeneity of the films. The development of a process for the quick production of large grain graphene in a commonly used commercial CVD reactor is a significant step towards an increased accessibility to millimetre-sized graphene crystals.